A method of predicting the image noise in paediatric multi-slice computed tomography images - Ledenius, K; Gustavsson, M; Johansson, S; Stålhammar, F; Söderberg, J; Wiklund, L M; Thilander Klang, A (Radiation protection dosimetry, 2005)
The purpose of this study was to develop an equation with which to determine the tube current to be used in order to obtain a certain image noise level for differently sized children undergoing multi-slice computed tomography examination. The relationship between image noise and detector dose for different examination protocols was established for a LightSpeed Ultra, an eight slice CT from GEMS, using homogeneous water phantoms of different sizes. Three different anatomical areas (head, thorax and abdomen) were studied in 111 patients between 0 and 17 y of age. The mean ratio between the calculated and the measured noise in patient images was established for the different areas. Head examinations showed the best correlation (measured-to-calculated noise ratio = 1.01). In the thorax, the calculated noise was generally higher than the measured noise (ratio = 0.74), and in the abdomen, the opposite result was found (ratio = 1.20).